2004
DOI: 10.1086/424999
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Human N-Acetyltransferase Genotype on the Early Bactericidal Activity of Isoniazid

Abstract: The elimination of isoniazid is subject to the influence of the N-acetyltransferase 2 (NAT2) genotype, and individuals may be homozygotic slow, heterozygotic fast, or homozygotic fast acetylators of isoniazid. The early bactericidal activity (EBA) of an antituberculosis agent can be determined by quantitative culture of Mycobacterium tuberculosis in sputum samples obtained from patients with pulmonary tuberculosis during the first days of treatment. In these studies, the EBA of isoniazid during the first 2 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 12 publications
3
55
0
2
Order By: Relevance
“…In accordance with this finding, increasing the daily INH dose up to 600 mg gave little increase in bactericidal effects, even in FA subjects, when the MIC was at the lower end of the MIC range. Those results are in accordance with clinical studies that found no increase in the EBA when the INH dose was increased beyond 150 to 300 mg per day (6,15,38). While those studies did not report the MICs of isolated strains of M. tuberculosis, we may hypothesize that those MICs were relatively low.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In accordance with this finding, increasing the daily INH dose up to 600 mg gave little increase in bactericidal effects, even in FA subjects, when the MIC was at the lower end of the MIC range. Those results are in accordance with clinical studies that found no increase in the EBA when the INH dose was increased beyond 150 to 300 mg per day (6,15,38). While those studies did not report the MICs of isolated strains of M. tuberculosis, we may hypothesize that those MICs were relatively low.…”
Section: Discussionsupporting
confidence: 89%
“…However, the need for INH dose optimization and adjustment for acetylator status is controversial. Clinical studies that assessed the EBA values with various doses of INH found that the EBA seems to plateau at 300 mg daily, as no significant increase in the EBA was observed with larger INH doses (6,15,38). However, it was shown that the EBA of INH in fast acetylators was significantly lower than that in slow acetylators (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, efficacy of isoniazid therapy seems to be better in SAs and significant differences in the mean early bactericidal activity of isoniazid between homozygous SAs and heterozygous or homozygous RAs could be demonstrated. 129 Individually tailored therapy with isoniazid, which could warrant optimal therapeutic efficiency and limitation of toxic effects, has not been used in clinical routine so far, although reliable genotyping or phenotyping approaches are available.…”
Section: Tuberculosis and Isoniazidmentioning
confidence: 99%